Design, synthesis, antimicrobial activity and computational studies of novel azo linked substituted benzimidazole, benzoxazole and benzothiazole derivatives. (February 2019) - Mishra, Virendra R.; Ghanavatkar, Chaitannya W.; Mali, Suraj N.; Qureshi, Shahnawaz I.; Chaudhari, Hemchandra K.; Sekar, Nagaiyan
Graphical abstract: Abstract: Novel azo linked substituted benzimidazole, benzoxazole, and benzothiazole were synthesized by diazo coupling and characterized by 1 H NMR, elemental analysis, FTIR and UV–vis spectroscopy. The newly synthesized compounds were evaluated for invitro antibacterial activity against Staphylococcus aureus and Escherichia Coli strains by Resazurin microtiter assay method (REMA). The minimum inhibitory concentration (MIC in μg/mL) were used to express the antibacterial activities. The azo linked compounds exhibited good to moderate or high antibacterial activities in vitro. Computational studies were performed to correlate HOMO-LUMO gap with antibacterial activity. The comparative molecular docking studies revealed better insights into binding mechanisms.